Is PROGRESA working? Summary of the results of an evaluation by IFPRI - Skoufias, Emmanuel; McClafferty, Bonnie (International Food Policy Research Institute, 2003)
Mexico’s Programa Nacional de Educación, Salud y Alimentación (PROGRESA) is a major government program aimed at developing the human capital of poor households. Targeting its benefits directly to the population in extreme poverty in rural areas, it seeks to alleviate current poverty through monetary and in-kind benefits, as well as to reduce future levels of poverty by encouraging investments in education, health, and nutrition. This chapter (based on Skoufias and McClafferty 2001) summarizes 24 months of extensive IFPRI research designed to evaluate whether PROGRESA has been successful in achieving its goals. The evaluation analyzed PROGRESA’s impact on education, health, and nutrition as well as in other areas, such as women’s status and work incentives (see Adato et al., Chapter 30).